Fixed-dose enoxaparin provides efficient DVT prophylaxis in mixed ICU patients despite low anti-Xa levels: A prospective observational cohort study - Jan Benes; Roman Skulec; Jakub Jobanek; Vladimir Cerny (Biomedical Papers, 2022)
Background. Deep vein thrombosis (DVT) is a serious but preventable complication of critical illness with a reported incidence from 4 to 17%. Anti-Xa activity in critically ill patients achieved with standard dosing of low-molecular-weight heparins (LMWH) is often below the target of 0.2-0.5 IU/mL. However, the clinical significance of this finding is unclear. The quality of thromboprophylaxis also strongly impacts the incidence of DVT. We performed a prospective observational study to evaluate the incidence of DVT in a mixed medical-surgical-trauma intensive care unit (ICU) using a thromboprophylaxis protocol with a fixed dose of enoxaparin. We also explored the relation between DVT incidence and anti-Xa activity. Method. All consecutive patients with expected ICU stay ≥72 hours and without evidence of DVT upon admission were included. They underwent ultrasound screening for DVT twice a week until ICU discharge, death, DVT or pulmonary embolism. Peak anti-Xa activity was measured twice a week. Patients received 40 mg of enoxaparin subcutaneously (60 mg in obese, 20 mg in case of renal failure). Graduated compression stockings were used in case of LMWH or another anticoagulant contraindication. Results. A total of 219 patients were enrolled. We observed six cases of DVT (incidence of 2.7%). The agreement between expected and delivered DVT prophylaxis was 94%. Mean peak anti-Xa activity level was 0.24 (SD, 0.13) IU/mL. There was no significant difference in anti-Xa activity in DVT and non-DVT group. Conclusion. A low incidence of DVT was achieved with meticulous adherence to the standard prophylactic protocol. The low incidence of DVT was observed despite low levels of anti-Xa activity. Our findings suggest that enoxaparin dose adjustment based on regular monitoring of anti-Xa activity is unlikely to result in further reduction of DVT incidence in a mixed ICU population. Trial registration: ClinicalTrials.gov, NCT03286985.